2021
DOI: 10.1155/2021/9951540
|View full text |Cite
|
Sign up to set email alerts
|

Possible Benefit of Angiotensin II Receptor Blockers in COVID-19 Patients: A Case Series

Abstract: Introduction. Dysfunction in the renin-angiotensin-aldosterone system (RAAS) has been observed in patients with coronavirus disease 2019 (COVID-19). It is presumed that the effect of reducing interleukin-6 (IL-6) levels by angiotensin II receptor blockers (ARBs) by RAAS modulation. We investigated changes in angiotensin II and IL-6 levels in four COVID-19 patients treated with ARBs. Case Presentation. Cases 1 and 2 were who had not received ARBs before and were newly administered ARBs. Case 3 restarted ARBs af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 43 A case series presented by Lee et al also indicated that patients treated with ARBs had reduced CRP following clinical improvement. 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 A case series presented by Lee et al also indicated that patients treated with ARBs had reduced CRP following clinical improvement. 44 …”
Section: Discussionmentioning
confidence: 99%
“…43 A case series presented by Lee et al also indicated that patients treated with ARBs had reduced CRP following clinical improvement. 44 Studies have demonstrated that the level of CRP measured upon admission is a straightforward and independent indicator that could be helpful for the early diagnosis of severity during COVID-19. 45,46 Yet; several studies suggested that rather than a single parameter, multiple markers should be used as predictors of severity and mortality in patients with COVID-19.…”
mentioning
confidence: 99%
“…Twenty two of these studies have already been completed. Some of the studies suggested reconsideration of ARBs in the treatment of COVID-19 patients and highlight the potential beneficial role of ARBs to improve the clinical outcomes of COVID-19 patients by controlling the RAAS (Renin-Angiotensin-Aldosterone System) dysfunction. , Other studies confirm safety of the ARBs treatment in COVID-19 patients this type of uncertainty suggesting that ARBs may worsen the condition of patients with COVID-19 arose at the beginning of the pandemic and has been refuted. In addition to clinical trials, molecular docking studies have also been conducted to demonstrate the potential of ARBs to inhibit the COVID-19 main proteasethe best results were obtained for fimasartan and candesartan …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of twenty-six studies involving 8,104 hypertensive ACEI/ARB users and 8,203 hypertensive non-ACEI/ARB users reported a significantly lower mortality risk and a lower need for ventilator use among ACEI/ARB users (Wang et al, 2021). Another study showed the possible benefit of ARBs in COVID-19 patients through a case series (Lee et al, 2021). There has been no studies regarding this in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%